Pseudogenes Functions and Protocols - Poliseno, Laura.; Poliseno, Laura. (Methods in Molecular Biology,, 2014)
Providing a list of methods useful both to those who wish to study pseudogenes and to those who actually want to avoid their inadvertent detection, Pseudogenes: Functions and Protocols explores techniques involving pseudogenic DNA, RNA, and peptides/proteins, once believed to lack any functionality, but now known to be involved in complex regulatory circuits. After a few introductory chapters that overview the functions so far attributed to pseudogenes, this thorough volume delves into methods for pseudogene identification, for the detection of pseudogene transcription and translation, and for the study of the functions of pseudogenic RNA and proteins, as well as methods to avoid pseudogene detection when the focus of the research is their highly homologous parental counterparts.  As part of the highly successful Methods in Molecular Biology series, chapters feature the kind of detailed descriptions and implementation advice that ensures successful results in the lab.   Authoritative and practical, Pseudogenes: Functions and Protocols will contribute to the high interest of the scientific community toward pseudogenes, while stimulating the conception of pseudogene-centered research projects and providing experimental protocols that can facilitate their execution.